Building Oral Health Research Capacity in India: Identifying Barriers and Enablers Using Mixed Methods - Masood M; Newton T; Kharbanda OP; Masood Y; Feine J; Gussy M; Lahti S (SAGE Journals, 2022)
This article will provide a brief overview of the methods in finding barriers and enablers in doing oral health research in India. This mixed-methods approach can be used by researchers in finding barriers and enablers in doing oral health research in other developing countries and building oral health research capacities.